Phanerozoic plate history and structural evolution of the Tarim Basin, northwestern China. Issue 12 (12th August 2020) - Wang, Tengfei; Jin, Zhenkui; Shi, Ziwei; Dai, Xiancai; Cheng, Rihui
ABSTRACT: As the largest inland oil-bearing basin in China, the Tarim Basin is a large-scale composite basin that has experienced a complex tectonic evolutionary history from the Ediacaran to the Cenozoic. From the Ediacaran to the Ordovician, the Tarim Basin was in an extensional tectonic environment. From the Silurian to the Devonian, the Tarim Block switched from the presence of passive margins to active margins along its northern and southern edges, eventually colliding with the North Kunlun Terrane in the Silurian. From the Carboniferous to the Triassic, the transition of the Tarim Block from an independent landmass to an internal component of the Eurasian Plate resulted from collisions with the Yili-Central Tianshan Terrane to the north during the Late Carboniferous and the Qiangtang Terrane to the south during the Triassic. From the Jurassic to the Paleogene, several unconformities developed because of the subduction of the Meso-Tethys oceanic plate during the Late Jurassic and the Neo-Tethys oceanic plate during the Paleogene. After the Neogene, as a rejuvenated foreland basin, the Tarim Basin was activated along its margins and became an intermountain basin due to the intense regional compression induced by the Indian Plate. Based on a seismic profile cross-section of the basin, we conclude that the extension and shortening in the profile reflects the block amalgamation history and the structural evolution of the Tarim Basin. The structural-sedimentary evolution of this basin is closely related to the movement of the peripheral plates.